Управување со патната инфраструктура и нејзино влијание врз економскиот развој на Република Македонија - Аручи, Седат (Економски факултет, УКИМ, Скопје, 2017)
The road infrastructure is a bloodstream of one national economy. All the motorways, regional roads and roads of a local character are in the function of the national economy. Thus, it is undisputable fact that the road infrastructure is of significant importance for each and every country. Having this into consideration, it is clear that in the case of the Republic of Macedonia, particular attention should be paid to the modernization of the road infrastructure, following the example of the developed countries in Europe and the world. It is certain that road infrastructure influences the economic development of each country. This means that a very good analysis should be made of the actual road infrastructure in the Republic of Macedonia because it is of great importance, and also it is necessary to make a rigorous planning of the further construction of new and contemporary roads. Critical criterion for such planning could be the trend and the practices of the developed European countries, but the countries and circumstances in the countries from the region should also be subjected to analysis. The analysis of the issues from scientific perspective, supported with data resulting from the Republic of Macedonia’s needs, all these compared to the global development trends is expected to result into certain appropriate suggestions and solutions about how to improve the actual condition the road infrastructure of the Republic of Macedonia is in. Hence, as an object of research in this paper there is an analysis of the meaning and finding an adequate way of managing the road infrastructure in general, and especially the example of R. Macedonia. It assumes an analysis of the current situation, as well as the development of the overall road infrastructure in Macedonia, as well as proposing measures for its improvement and modernization in the function of economic development.
Road infrastructure management and its impact on the economic development in the Republic of Macedonia
Докторска дисертација одбранета во 2017 година на Економскиот факултет во Скопје, под менторство на проф. д–р Пеце Недановски.
Keywords: road infrastructure, economic development, governance, Republic of Macedonia